1968
DOI: 10.1063/1.1669990
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Phase Transition in KH2PO4

Abstract: The high-temperature phase transition in KH2PO4 has been investigated by differential thermal analysis, thermogravimetric analysis, proton magnetic resonance and relaxation, infrared spectroscopy, and x-ray and quasielastic cold-neutron scattering. The transition is not connected with a static breaking up of the hydrogen-bond network but rather with the onset of disordered hindered rotation of the H2PO4 groups around all three axes. It seems that rotation of H2PO4 groups is as well rate determining for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In figure 2b, the TGA and DTA curves of pure potassium dihydrogen phosphate, (KH 2 PO 4 ) are presented. The peaks in the DSC curve below 200 °C have previously been identified as due to a phase transition involving the onset of disordered hindered rotation of H 2 PO 4 groups around all three axes [23]. It is also observed that at higher temperatures, approximately above 200 °C, the DTA curve bends downwards indicating thermal decomposition of KDP as previously reported earlier [24].…”
Section: Resultsmentioning
confidence: 58%
“…In figure 2b, the TGA and DTA curves of pure potassium dihydrogen phosphate, (KH 2 PO 4 ) are presented. The peaks in the DSC curve below 200 °C have previously been identified as due to a phase transition involving the onset of disordered hindered rotation of H 2 PO 4 groups around all three axes [23]. It is also observed that at higher temperatures, approximately above 200 °C, the DTA curve bends downwards indicating thermal decomposition of KDP as previously reported earlier [24].…”
Section: Resultsmentioning
confidence: 58%
“…The aim of our work is to obtain more insight into the relaxation behaviour of KDP, in which the rotation of the 2 4 H PO − radicals has been claimed to be important [5]. If the complex permittivity representation of measured dielectric data is used a relaxation is detected as a step in the real part and a peak in the imaginary part of the permittivity.…”
Section: Nhmentioning
confidence: 99%
“…Relaxation time data for we~ker shocks were collected with a thin-film resistance thermometer mounted flush in the end wall; both a bare platinum film and a platinum film insulated with about 8000 1 of SiOz were used. 3 Typical experimental records of wall pressure and temperature are shown in Fig. 1.…”
Section: Ionization Relaxation Time Measurements In Neonmentioning
confidence: 99%